Efficacy of pulsed dye laser in cosmetically distressing facial dermatoses in skin types IV and V - Khandpur Sujay; Sharma Vinod (Wolters Kluwer Medknow Publications, 2008)
Background: Pulsed dye laser (PDL) has revolutionized treatment of vascular dermatoses. It has been successfully employed to treat several non-vascular conditions in fair skinned individuals without producing significant pigmentary and textural complications. Aim: A preliminary study was undertaken to assess its efficacy in cosmetically distressing facial, vascular and non-vascular dermatoses in Indian patients with skin types IV and V. Materials and Methods: Nine patients of ages 7 to 55 years, with facial verruca plana (VP- 4 cases), angiofibromas (AF- 4 cases) and multiple pyogenic granulomas (PG- one case) were recruited. They had no systemic complaints. Laser parameters used were (spot size/fluence/wavelength/pulse duration):VP- 5mm/5.5-7.5J/585nm/0.45ms; AF-5mm/6-8.5J/585nm/0.45ms;PG- 5mm/7J/585 and 595nm alternately/1.5ms. Response was assessed clinically and photographically. Results and Conclusions: All VP lesions completely resolved after 2-4 sessions (mean 3.25 sessions), AF showed 50% regression in all cases after 2-3 sessions (mean 2.5 sessions) and ≥75% subsidence after 3-7 sessions (mean 5.5 sessions) and in PG, after 3 sessions, there was complete subsidence of small satellite lesions with moderate shrinkage of larger papules and complete resolution after 5 sessions. Complications included transient hyperpigmentation/hypopigmentation only. There was no recurrence during next 6 months. PDL offers significant cosmetic improvement in facial dermatoses in Indian patients.